CONTRACEPTION PRACTICES IN RELATION TO SOCIODEMOGRAPHIC VARIABLES AND WOMEN EMPOWERMENT - Amin, Nabila; Johar, Nigar; Mashhadi, Syed Fawad; Shams, Mehwish Ara (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the autonomy of young Pakistani women in house hold decision making and the use of modern contraception; and to find association between couples’ joint participation in decision making and use of modern contraception. Study Design: Cross-sectional study. Place and Duration of Study: Pak Emirates Military Hospital, Rawalpindi, from Aug 2018 to Aug 2019. Methodology: The study took place at Gynae & Obstetrics department Pak Emirates Military Hospital, Rawalpindi from Aug 2018 to Aug 2019. Cross-sectional study design was adopted. Results: Out of 360 women, 179 (49.7%) had 3-5 children while only 17 (4.7%) had more than 6 children. According to 261 (72.5%) women both husband and wife wanted same number of children while in only 2 (0.6%) cases husband wanted fewer children. Socioeconomic status showed a statistically strong association (p=0.035) with using modern contraceptives. Education status showed a statistically strong association with desire for more children (p=0.004), usage of modern contraceptives (p=0.004) and respondents role in household decision making (p=0.041). Conclusion: It was found that in substantial number of couples decision for usage of modern contraceptives was mutual. A very alarming finding was that most of the women have not had an encounter with family planning worker in last six months despite the fact that most of the women in the study did not have desire to have more children.